Targeting TNF-related apoptosis-inducing ligand (TRAIL) receptor by natural products as a potential therapeutic approach for cancer therapy - Dai, Xiaoyun (Exp Biol Med (Maywood), 2015)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to selectively induce apoptotic cell death in various tumor cells by engaging its death-inducing receptors (TRAIL-R1 and TRAIL-R2). This property has led to the development of a number of TRAIL–receptor agonists such as the soluble recombinant TRAIL and agonistic antibodies, which have shown promising anticancer activity in preclinical studies. However, besides activating caspase-dependent apoptosis in several cancer cells, TRAIL may also activate nonapoptotic signal transduction pathways such as nuclear factor-kappa B, mitogen-activated protein kinases, AKT, and signal transducers and activators of transcription 3, which may contribute to TRAIL resistance that is being now frequently encountered in various cancers. TRAIL resistance can be overcome by the application of efficient TRAIL-sensitizing pharmacological agents. Natural compounds have shown a great potential in sensitizing cells to TRAIL treatment through suppression of distinct survival pathways. In this review, we have summarized both apoptotic and nonapoptotic pathways activated by TRAIL, as well as recent advances in developing TRAIL–receptor agonists for cancer therapy. We also briefly discuss combination therapies that have shown great potential in overcoming TRAIL resistance in various tumors.